A model-based approach to teaching about solutions. (3rd July 2022) - Eymur, Gülüzar; Capps, Daniel K.
Abstract: We present an example of a novel, model-based approach to instruction in which learners constructed a representation of a specific phenomenon, evaluated their representation, and then revised it, via an abstraction process, to construct a model. The example took place in high school in the context of solution chemistry. The aim of the instruction was to support students in developing a generalized model for a homogenous mixture where the ratio of the solute and solvent remains the same throughout the solution. Students also developed a general model of the effect of pressure and temperature on solubility. Pre- and posttests were administered to provide evidence of student learning because of the experience.